A relevância de Domício da Gama e de seus contos para o estudo do impressionismo literário no Brasil - Caetano, Ricardo Welinton (2023)
A study proposition about Domício da Gama could begin with several scenarios, whether from his relevance as a diplomat or from his contribution as a journalist. However, what is intended here is to provide a meaningful approach to his contribution, as a writer, to Brazilian literature, especially to literary impressionism in Brazil. Reflecting on the relevance of Domício's work aims to rectify the injustice done to a writer whose value was recognized during his lifetime, but which unfortunately faded away over the years after his death. Therefore, the research focus on the first phase of the writer, a period in which literary impressionism was more pronounced in his work, especially in the short stories published between 1886 and 1898. In order to do this, it is essential to briefly explain what impressionism is, from its origins in painting to its manifestation in other arts, especially literature, in order to support its existence in Domício's work. Among the short stories written during this period, we will focus on "The Song of the King of Tule", "Scherzo", "Tale of Truth" and "Alma Nova", because they all share a common feature: the use of sound as a way of broadening the sensory experience of fictional entities. Consequently, it is necessary to turn to narrative theories for an analysis of the narrative process of these short stories, especially the types of narrator and focalization employed by them.